Kontradiksi Regulasi TKDN dalam Perizinan Impor di Indonesia: Analisis Yuridis Normatif Terhadap Hukum Perdagangan dan Penanaman Modal - Angel Anandra (CV Rewang Rencang, 2025)
This study aims to analyze the regulatory contradictions in the implementation of Indonesia’s Local Content Requirement (TKDN) as a prerequisite for import licensing. The research focuses on the conflict between national industrial protection policies and Indonesia’s commitments under international trade law and investment principles. Externally, the TKDN policy potentially violates the National Treatment principle under Article III of the General Agreement on Tariffs and Trade (GATT) 1994 and the prohibition of performance requirements under the Agreement on Trade-Related Investment Measures (TRIMs). Internally, the implementation of TKDN as a licensing condition raises issues concerning the principles of legal certainty and transparency, as guaranteed by Law No. 25 of 2007 on Investment. This research employs a normative juridical method, utilizing both the statute approach and the conceptual approach. The data sources consist of primary, secondary, and tertiary legal materials analyzed through qualitative descriptive interpretation of relevant legal norms and regulatory synchronization. The findings reveal a significant normative contradiction between TKDN as a protective industrial policy and Indonesia’s obligations under international trade law, as well as domestic investment principles that ensure legal certainty. The study concludes that regulatory harmonization is necessary to align TKDN policy with principles of trade liberalization and a fair, competitive investment climate.